Strategic Decision Making: The Effects of Cognitive Diversity, Conflict, and Trust on Decision Outcomes - Olson, Bradley J.; Parayitam, Satyanarayana; Yongjian Bao (Journal of Management, 2007)
Basing their hypotheses on information processing theory, the authors incorporate important group processes within strategic decision making. They examine the interrelationships of cognitive diversity, task conflict, and competence-based trust and their effects on decision outcomes. Their survey includes top management teams from 85 U.S. hospitals. They found that cognitive diversity has a strong positive relationship with task conflict and that competence-based trust strengthens this relationship. In addition, these results suggest that task conflict mediates the effects of cognitive diversity on decision outcomes.